Ibère, grec et latin à Toulouse à la fin du iie s. av. J.-C. : nouvelles inscriptions sur céramique du site de la ZAC Niel - Pierre Moret; Coline Ruiz Darasse; Guillaume Verrier (Gallia)
The excavation conducted in 2009-2011 at the ZAC Niel in Toulouse (Haute-Garonne) yielded varied and original epigraphic writings. Responding to the finds of the last excavations in Toulouse’s urban area in the early 1980s, these writings on ceramics testify the use of three kinds of writings in Tolosa at the end of the 2nd c. BC: Paleohispanic, Latin and Greek, proofs of an outstanding diversity of writing practices. A particular graffiti we studied held our attention, as it could be either a graphic exercise showing that on this site existed a learning school of Paleohispanic writing, or a Celtic name written in Iberian.